Reducing Handoff Delay In WLan Using Selective Proactive Context Caching - Ling, Teck Chaw; Lee, Jen Funn; Hoh, Kian Pee (Malaysian Journal of Computer Science, 2010)
In IEEE 802.11 wireless networks, continuous connectivity which allows user mobility and maintains network utilization is one of the most important requirements. In order to establish and keep service state information during the handoff process, the context transfer protocol is used to transfer service state from the originally associated base station to another base station. These base stations exchange messages to establish a secure channel between the APs for transmitting the STA context information. The entire process, however, inevitably increases the overall handoff latency. To resolve the predicament, we propose the Selective Proactive Context Caching (SPCC) technique to proactively propagate security context of the mobile client to a selected set of neighboring base stations before re-association occurs. Unlike the conventional 802.11 handoff mechanism in which cooperation among neighboring base stations does not exist, a selected neighboring base stations in SPCC exchange link quality information of the mobile client through LAN and this information is stored into cache memory. Based on the link quality information, the originally associated AP selects a set of neighboring APs and forwards the security context of mobile station through the LAN. Simulation results show an improvement of 62% in reducing the re-association handoff delay. Specifically, the re-association delay is reduced from 3.2 ms in the 802.11 handoff mechanism to 1.2 ms when SPCC is applied.